2023
DOI: 10.3390/pr11010163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self-Fabricated Graphene–Metal Oxide Composite Anodes on Metal Degradation and Energy Generation via a Microbial Fuel Cell

Abstract: Microbial fuel cells (MFCs) are thought to be ecologically friendly, despite electron transport and generation challenges. In order to address this, the efficiency of MFCs was investigated using two different anode electrodes made from biomass: graphene oxide (GO) and graphene oxide-metal oxide (GO-MO) (GO-ZnO). After 18 days of operation, the maximum power density for GO was 0.69 mW/m2, whereas the maximum power density for GO-ZnO was 1.05 mW/m2. Furthermore, the ability of MFCs to transform the soluble metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The anode electrodes of carbon, graphene, graphite and derivatives are the most used materials as anodes in MFCs due to their high biocompatibility for microbial growth owing to their surface characteristics (roughness) and electrical conductivity [80]. An immense amount of carbon research has been conducted in three ways: carbon felt, carbon cloth and carbon paper [81]. Currently, electrodes with metallic nanoparticles or metal plates are being researched because they offer a low cost in the market.…”
Section: Results and Analysismentioning
confidence: 99%
“…The anode electrodes of carbon, graphene, graphite and derivatives are the most used materials as anodes in MFCs due to their high biocompatibility for microbial growth owing to their surface characteristics (roughness) and electrical conductivity [80]. An immense amount of carbon research has been conducted in three ways: carbon felt, carbon cloth and carbon paper [81]. Currently, electrodes with metallic nanoparticles or metal plates are being researched because they offer a low cost in the market.…”
Section: Results and Analysismentioning
confidence: 99%
“…Likewise, using bianodes in MFCs has also been reported to improve the efficiency of the cells because by placing two anodes, the adhesion of electrons would increase, thus obtaining a greater flow of electrons. However, a problem has been observed in the reaction of these electrodes because the cathode tends to show faster wear compared to cells with a single anode [56,57]. Other researchers have reported that the coating of the metal electrode with carbon or graphite improves the adhesion of electrons because the porosity shown by these two materials adheres a more significant number of electrons than when passing to the metallic material if it repowers because the metal or non-metallic nanoparticles embedded in the carbon or graphite electrode show lower resistance to the passage of electrons [58,59].…”
Section: Results and Analysismentioning
confidence: 99%
“…The production of energy from the MFC was still below expectations because of the material that was employed for the electrodes. The material that is utilized for the electrodes, in particular the anode, should have the capability of transporting electrons more effectively while simultaneously creating a biocompatible environment in which bacteria may form biofilm around the anode surface [68]. Recently, the electrode material that is made from biomass has been the topic of the most promising conversations due to its efficiency, cost, and performance.…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%